FUNCTIONAL MORPHOLOGY AND MOLECULAR DYNAMICS OF THE ADRENAL CORTEX: A STRUCTURAL STUDY ON STRESS-INDUCED HORMONAL IMBALANCE (Modern American Journal of Medical and Health Sciences, 2026)
Stress-induced activation of the hypothalamic-pituitary-adrenal (HPA) axis leads to profound structural and molecular shifts within the adrenal cortex. This study utilizes an integrated approach, combining histomorphological evaluation with 100 ns molecular dynamics (MD) simulations to investigate cellular adaptation and the stability of glucocorticoid receptor (GR) interactions. Our findings reveal that chronic stress triggers significant hypertrophy in the zona fasciculata, while MD analysis confirms that the hormone-receptor complex maintains high thermodynamic stability (Delta G = -42.6 kcal/mol) despite structural fluctuations. These results provide a robust framework for understanding the "histo-architectonics" of stress adaptation.